THE RELATIONSHIP BETWEEN RISK AVERSION AND BRAND LOYALTY IN MEN’S CARE PRODUCTS - Dwi Anna Kristanti (Jurnal Manajemen Pemasaran, 2023)
Developing e-commerce platforms in Indonesia has also contributed to the growth of the cosmetic and personal care product sector. Currently, cosmetic products are no longer only intended for women but also men. Thus, creating opportunities and a conducive environment for the emergence of new companies. With the increasing number of companies in the men's cosmetic industry today, building brand loyalty is one of the biggest challenges companies will face. This study aims to explore the relationship between risk aversion and brand loyalty and test whether this relationship is mediated by brand trust and brand affect in men's purchase of cosmetic and body care products. The sample selection was carried out using a purposive sampling method with 130 respondents with the criteria of being male students in Surabaya. Data analysis using SEM-PLS variant-based structural equation method. The results showed that risk aversion is statistically significant in influencing brand trust, brand affect, and brand loyalty. Brand trust and brand affect are also statistically significant in influencing brand loyalty. By analysing brand loyalty and the variables that influence it, cosmetic and men's body care product companies can understand how to develop brand loyalty, especially by paying attention to risk aversion, brand trust, brand affect, and brand loyalty.